Vascular Endothelial Growth Factor A Signaling Promotes Spinal Central Sensitization and Pain-related Behaviors in Female Rats with Bone Cancer. (November 2019) - Hu, Xue-Ming; Yang, Wei; Du, Li-Xia; Cui, Wen-Qiang; Mi, Wen-Li; Mao-Ying, Qi-Liang; Chu, Yu-Xia; Wang, Yan-Qing
Abstract : Background: Cancer pain is a pervasive clinical symptom impairing life quality. Vascular endothelial growth factor A has been well studied in tumor angiogenesis and is recognized as a therapeutic target for anti-cancer treatment. This study tested the hypothesis that vascular endothelial growth factor A and vascular endothelial growth factor receptor 2 contribute to bone cancer pain regulation associated with spinal central sensitization. Methods: This study was performed on female rats using a metastatic breast cancer bone pain model. Nociceptive behaviors were evaluated by mechanical allodynia, thermal hyperalgesia, spontaneous pain, and CatWalk gait analysis. Expression levels were measured by real-time quantitative polymerase chain reaction, western blot, and immunofluorescence analysis. Excitatory synaptic transmission was detected by whole-cell patch-clamp recordings. The primary outcome was the effect of pharmacologic intervention of spinal vascular endothelial growth factor A/vascular endothelial growth factor receptor 2–signaling on bone cancer pain behaviors. Results: The mRNA and protein expression of vascular endothelial growth factor A and vascular endothelial growth factor receptor 2 were upregulated in tumor-bearing rats. Spinal blocking vascular endothelial growth factor A or vascular endothelial growth factor receptor 2 significantly attenuated tumor-induced mechanical allodynia (mean ± SD: vascular endothelial growth factor A, 7.6 ± 2.6 g vs. 5.3 ± 3.3 g; vascular endothelial growth factor receptor 2, 7.8 ± 3.0 g vs. 5.2 ± 3.4 g; n = 6; P < 0.0001) and thermal hyperalgesia (mean ± SD: vascular endothelial growth factor A, 9.0 ± 2.4 s vs. 7.4 ± 2.7 s; vascular endothelial growth factor receptor 2, 9.3 ± 2.5 s vs. 7.5 ± 3.1 s; n = 6; P < 0.0001), as well as spontaneous pain and abnormal gaits. Exogenous vascular endothelial growth factor A enhanced excitatory synaptic transmission in a vascular endothelial growth factor receptor 2–dependent manner, and spinal injection of exogenous vascular endothelial growth factor A was sufficient to cause pain hypersensitivity via vascular endothelial growth factor receptor 2–mediated activation of protein kinase C and Src family kinase in naïve rats. Moreover, spinal blocking vascular endothelial growth factor A/vascular endothelial growth factor receptor 2 pathways suppressed protein kinase C-mediated N -methyl-D-aspartate receptor activation and Src family kinase-mediated proinflammatory cytokine production. Conclusions: Vascular endothelial growth factor A/vascular endothelial growth factor receptor 2 contributes to central sensitization and bone cancer pain via activation of neuronal protein kinase C and microglial Src family kinase pathways in the spinal cord. Abstract : In a female rat model of metastatic breast cancer, expression of vascular endothelial growth factor A and its receptor vascular endothelial growth factor receptor 2 were upregulated in spinal tissue. Blocking vascular endothelial growth factor signaling improved several measures of nociception and function in this model suggesting a role for vascular endothelial growth factor antagonists in reducing cancer-related pain.